Pathways linking climate change and HIV/AIDS: An updated conceptual framework and implications for the Philippines - Guinto, Renzo R; Cahatol, Joshua Joel F.; Lazaro, Kris Yvan Mari S.; Salazar, Anna Flora Natividad Cruz (Elsevier, 2022)
As we commemorate the 40th anniversary of the discovery of Human Immunodeficiency Virus (HIV) while fighting the ongoing COVID-19 pandemic, another global crisis - climate change - is threatening the progress achieved so far in the global fight against HIV/AIDS. The climate emergency is anticipated to generate dire health consequences worldwide in the coming decades. While the pathways that link climate change and different disease areas are better understood, the connection between climate change and HIV/AIDS is still yet to be recognized both in research and practice. In this review, we update one of the frameworks on the HIV-climate nexus described in earlier literature. Four major pathways have been identified: extreme weather events; sea level rise; changes in precipitation and temperature; and increased air pollution. These pathways impact the spectrum of HIV/AIDS-related outcomes through changes in social systems, healthcare disruption, and other climate-sensitive diseases, influenced by the social determinants of health. We also reflect on the significance of this updated framework for the Philippines, a country that is both highly vulnerable to the climate crisis and facing a rising HIV/AIDS epidemic. The framework can aid countries like the Philippines in filling gaps in research, policy, and program design to mount climate-adaptive HIV/AIDS responses. The HIV/AIDS and climate justice movements must also join forces in calling for accelerated worldwide decline in greenhouse gas emissions from all sectors to stabilize the global climate - this will benefit not just people affected by HIV/AIDS but everyone.